HUMAN TO HUMAN WHISPERS FROM ‘PESANTREN’ CHAMBERS: LOCALITY IN IDEOLOGICAL VOICES OF THE AUTHORS AS A COMMUNICATION IN HUMAN CIVILIZATION - Hat Pujiati (International Conference on Languages and Arts, 2014)
This article is a part of my research entitled Model Pengembangan Komunitas Sastra Berbasis Lokalitas: Meretas Jalan bagi Industri Kreatif Kesastraan di Wilayah Tapal Kuda that find models of literary works develops in literary communities based on locality in Horseshoe area, East Java so that I can map and design their dessemination nationally and Indternationally.  In this article I discusses literary works authored by those who live in ‘Pesantren’ in Jember and Situbondo, East Java, as medium of practicing language in Pesantren community. Through the voices presented in Tartila, a novel by Arifa from Al-Falah Jember and in poetry anthology entitled Kasidah Air Mata by Zainul Walid from Pesantren Salafyah Syafi’iyah Sukorejo- Situbondo, this article questions the following three questions in order to find the ideology of the authors with their locality as a means to humanize human in human civilization. Firstly, it elaborates how locality is presented in the two works. Secondly, it demonstrates authors’ world views (Vision du Monde) on humanity. Thirdly, it digs out the causes of the world views existence on those authors. Lucien Goldmann’s genetic Structuralism is used in this article to analyze the data, and Derrida’s deconstruction is used as the method. Meanwhile, postcolonial concepts are used to explain condition of hybrid identity in a part of horseshoe area (Banyuwangi-Jember-Situbondo)   Keywords: ideology, pesantren,World view, genetic structuralism, hybrid